Prejudice and attitudes of medical students about alcohol use - Genişol, Esra; Yargıç, İlhan and Saka, Ömer and Sivri, Fazilet and Güleryüz, Şebnem and Işıl, Gürhan and Baraz, Esra and Dağlıgöz, Gökçe and Aslanargün, Pınar and Güvenç, İlker (Journal of Dependence, 2003)
Object: Alcohol use disorders are common and lead to multiple hospital applications for various reasons. Research data shows that these patients are not sufficiently recognized at the health care services they have been applied to. This ineffective care may be related to physicians’ own experiences and attitudes towards the subject. Method: A questionnaire about alcohol use and related stigma, prepared by Finland Medical Students Association and was approved to be an international project by International Federation of Medical Students was handed out to 1012 medical students from seven different medical faculties in five different cities by the members of Turkish Medical Students Association. Results: Our data shows that the amount of alcohol consumption, clinically harmfull is quite common among medical students. Moreover, 40% of these students don’t think that it is necessary to refer the alcoholic patients for medical treatment. Conclusion: We believe, these doctors of the future should be better educated to give better health care to these patients.